Modernism and time : the logic of abundance in literature, science, and culture, 1880-1930 - Schleifer, Ronald (Cambridge University Press, 2000)
Modernism and Time offers a powerful reassessment of the politics and culture of modernism across a broad range of disciplines. Ronald Schleifer examines changing conceptions of temporality in post-Enlightenment thought and engages with the work of writers and thinkers as diverse as George Eliot, Walter Benjamin, Einstein and Russell.